A 'SOURCE AND APPLICATION OF FUNDS' PHILOSOPHY OF FINANCIAL ACCOUNTING. - Carson, A. B. (The Accounting Review, 1949)
Abstract Financial accounting can be regarded as essentially a process of keeping historical records of financial stewardship. Since working capital is such an important matter, the records should be maintained and various statements prepared in a manner that will not obscure the movement of working capital funds. The calculation of periodic income is a secondary function. This viewpoint leads to what may be termed a source and application of funds concept or philosophy of financial accounting. It involves nothing essentially new except a shift of emphasis. Most of the current principles and practices can be regarded in this light. An unqualified adoption of this viewpoint suggests some modifications of current practice. Both the income statement and the balance sheet may be restated to emphasize the fund change, or fund flow, aspect of business undertakings. The source and application of funds statement itself gains in significance. The double entry bookkeeping process may be invested with a source-application meaning. Debits (apart from those made in the income summarizing process) can be interpreted as expressions of applications of funds, and credits (with the same qualification), as sources. It this is done, certain matters that are sometimes formally recorded would not be recognized in the accounts proper. The source-application of funds viewpoint narrows the gull between accounting for business organizations and for non-business undertakings, as well as for fiduciaries. Without adopting or accepting all of the possible variations of existing practice that have been suggested, the source and application of funds philosophy may be used as merely one measure or standard by which accounting principles and practices, existing and proposed, may be evaluated.